Identifikasi Lumut Kerak (Lichen) sebagai Bioindikator Pencemaran Udara di Area Kampus Universitas Islam Negeri Sunan Gunung Djati - Allifa Khoerurrahmah; Amelia Alphabenita; Clarissa Syahnaz Aulia; Ateng Supriyatna (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to identify lichens as bioindicators of air pollution in the area of ​​the Sunan Gunung Djati State Islamic University Campus, Bandung. Research was carried out to evaluate the amount and types of lichen present and to assess the air quality in the campus environment. In this research, observations were made of several types of lichens growing in various locations on campus. Observation results showed the presence of several types of lichens such as Dirinaria sp., Cryptothecia striata, Dirinaria picta, and Diploicia canescens. The number of colonies and morphological characteristics of each lichen type were identified to interpret the level of air pollution at each location. Observation results show that the campus has a variety of lichen types, each of which shows tolerance to different environmental conditions. Among the types found, Dirinaria sp. and Cryptothecia striata were found in relatively large numbers of colonies, while Dirinaria picta showed good adaptability even though it was found in small numbers, and Diploicia canescens indicated fairly polluted air conditions. Thus, this research concludes that lichens can be used effectively as bioindicators to monitor air quality around campus, with the number and diversity of lichen types providing an overview of overall environmental conditions.